As condições de vida durante a infância e seu impacto na estatura adulta das mulheres na América Latina - Mario Ernesto Piscoya Diaz (2011)
Living conditions during the early childhood and younger ages has become a very important issue due to the effects they have on health and socioeconomic events that take place during the adulthood and the elderly. Several indicators have been used to measure the well-being of populations, but there is a consensus that adult height is the indicator that describes the most important aspects of epidemiological and socioeconomic conditions experienced through childhood, because its final value it is affected by those conditions.The main objective of this work is to assess the association between female adult height and the living conditions experienced during childhood and younger ages in eleven countries in Latin America. The analysis focus on average female adult height from cohorts born between 1960 and 1985 in those countries. In this work, living conditions were approximated by nutrition, health, socioeconomic and urbanization conditions observed when each cohort was zero (0), five (5), ten (10) and fifteen (15) years old. From aggregate data in a country level, a regression model suggested by Akachi & Canning (2008) was used to establish the relationship between adult height and the indicators observed when the cohorts were zero, five (5), ten (10) and fifteen (15) years old. As that model presents a methodological limitation (colinearity) we consider the principal component analysis method to avoid that limitation. Results showed an improvement of living conditions during the childhood in all the countries. However, the increase in female adult height was not observed in all of them. Results also show the persistence of nutritional inequality in each country in the region, inequalities that can be translated in socioeconomic differences in adult height.